A vida escrita do poeta escravo Juan Francisco Manzano: caminhos, pedras e versos - Costa, Silvia Maria Fernandes Alves da Silva (2021)
This thesis presents a study on the composition of the Autobiografía de un esclavo (Autobiography of a Slave), by the Cuban poet Juan Francisco Manzano (1797?-1853), in order to determine the creative procedures of the work and verify the possibility of his autobiographic text as a foundational work in Latin America, building a black identity and memory, thus becoming a subversive written document during colonial times. Therefore, we have used a basic nature methodology, a qualitative approach, an exploratory level and bibliographical investigation procedures, which have given theoretical support to the discussion, elucidating the issue in this study, aiming to explain the corpus of this study and to recognize Manzano’s self-portrait (or image), both direct and indirectly. The autographical text of Manzano was written in 1835 with support of the literary critic Domingo del Monte (1804-1853) and was published in London in English in 1840, as the Spanish metropolitan censorship would not allow the publication of texts with slavery content in Cuba. However, the first publication in the Spanish language happened in Havana in 1937, based on the autographical text. It was also based on this text, which is at the National Library José Martí in Havana, that William Luis did its publication in 2007 with all the amendments and corrections that this text presents. It is based on Luis’ publication that this thesis unfolds, firstly, from the perspective of “autobiographical pact”, by Philippe Lejeune (1994), that the authenticity of Manzano’s autobiography was proved, by fulfilling this pact. Furthermore, we have used seven of Manzano’s letters to Del Monte to support this analysis and reveal his direct image. Furthermore, it has established the autobiographical space of the poet in a possible dialogue between his only published theatrical play, Zafira (1842) – supposedly a story of African colonization – and seven selected poems written by Manzano with antislavery background, all analyzed under the post-colonial bias to detach the poet’s indirect image. Finally, this study has examined Manzano’s autobiography under the optics of the psychodynamics of orality relative to the psychodynamics of writing which, according to Walter Ong (1998), diverge, what has allowed to determine the fundamentals of Latin American literary writing, being Manzano and his writing of significant importance in the role of constructing the identity of the black in the Americas.